Application of the Manova multivariate technique to two control variables from three simulation models of a productive process (2020)
In this article, the improvement of the manufacturing process of a construction brick producing company in the city of Santa Marta was studied. By simulation, the current process has been modeled and improvement alternatives have been established. The performance of these simulated processes has been assessed using the variables cost per lot (in Colombian pesos) and the time in the System (in hours), both programmed in the simulated models and which were established as control variables. These variables are the components of a bivariate vector whose values were obtained from samples derived from replicating each of the models, which were then analyzed using a technique derived from multivariate statistics called Manova. The multivariate hypothesis test shows that one of the models presents better performance. Based on the results, it is concluded that the company should adopt the improvement found in the simulation.